1999
DOI: 10.1016/s0014-5793(99)00302-6
|View full text |Cite
|
Sign up to set email alerts
|

Amber mutations in ribosome recycling factors of Escherichia coli and Thermus thermophilus: evidence for C‐terminal modulator element

Abstract: Ribosome recycling factor, referred to as RRF, is essential for bacterial growth because of its activity of decomposition of the post-termination complex of the ribosome after release of polypeptides. In this study, we isolated a conditionally lethal amber mutation, named frr-3, in the Escherichia coli RRF gene at amino acid position 161, showing that the truncation of the C-terminal 25 amino acids of RRF is lethal to E. coli. An RRF gene cloned from Thermus thermophilus, whose protein is 44% identical and 68%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 21 publications
3
39
0
Order By: Relevance
“…By contrast, an excess of IF3 alone dissociates 70S ribosomes [18 and 35]. A recent report has shown that Thermus thermophilus RRF, which does not function in Escherichia coli in vivo [36], can complement the defective E. coli RRF if a plasmid expressing IF3 is present [37]. Because T. thermophilus RRF, together with E. coli EF-G and ribosomes, functions only to release tRNA [38], an excess of IF3 might disassemble the 70S ribosomes left on mRNA without tRNA.…”
Section: Dissociation Of Ribosomes Into Subunits By Rrf and Ef-gmentioning
confidence: 99%
“…By contrast, an excess of IF3 alone dissociates 70S ribosomes [18 and 35]. A recent report has shown that Thermus thermophilus RRF, which does not function in Escherichia coli in vivo [36], can complement the defective E. coli RRF if a plasmid expressing IF3 is present [37]. Because T. thermophilus RRF, together with E. coli EF-G and ribosomes, functions only to release tRNA [38], an excess of IF3 might disassemble the 70S ribosomes left on mRNA without tRNA.…”
Section: Dissociation Of Ribosomes Into Subunits By Rrf and Ef-gmentioning
confidence: 99%
“…The ttRRF protein was overproduced in a bacterial expression system (Fujiwara et al+, 1999)+ E. coli BL21(DE3) transformed with pET30-ttRRF plasmid was grown at 37 8C to the cell density of 0+7 A 600 + Expression of ttRRF was induced by addition of isopropyl-1-thio-b-D-galactoside (final 0+5 mM), followed by 3 h culture at 37 8C+ Harvested cell paste (2 g) was suspended in 16 mL of buffer A (50 mM Tris-HCl, pH 7+0, 10 mM MgCl 2 , 5 mM b-mercaptoethanol) containing 500 mM NH 4 Cl, and sonicated+ The cell debris and ribosomes were removed from the cell lysate by two successive centrifugations (16,000 ϫ g for 20 min and 100,000 ϫ g for 30 min)+ The supernatant was heated at 65 8C for 15 min and denatured E. coli proteins were removed by centrifugation+ Crystalline ammonium sulfate was added to the cleared supernatant up to 1+5 M and the protein solution was loaded onto a ButylToyopearl column (10 mL)+ A linear gradient of 1+5-0 M ammonium sulfate in buffer A was used for elution+ Fractions containing ttRRF were combined, dialyzed against buffer A, and were further purified on a Heparin-Ultragel column (15 mL) using a linear gradient of 0-1 M NH 4 Cl in buffer A+ The protein was purified to near homogeneity with impurity less than 3% as judged by SDS-polyacrylamide gel electrophoresis, and concentrated to 10-15 mg/mL+…”
Section: Protein Expression and Purificationmentioning
confidence: 99%
“…Platinum sites were identified by Bijvoet difference Patterson interpretation with SHELX-97 using data between 50 and 4+0 Å resolution+ The refinement of heavy atom positions and calculations of MAD phases were carried out with MLPHARE (Collaborative Computational Project, Number 4, 1994) using 50-3+0 Å resolution data+ These initial phases were refined by solvent flattening and histogram matching with DM (Collaborative Computational Project, Number 4, 1994)+ At first, solvent content was set to 50-60% of the unit cell for the calculated value of 60%+ In an electron density map, three long helices (about 100 residues) were easily traced, but other parts were not observed+ Then we tried solvent flattening again with lower solvent contents, 5, 10, 20, 30, and 40%, to prevent a weak electron density in the molecular region from being flattened+ The best results were obtained with 20% solvent content+ An initial model consisting of 130 residues was built in the electron density map using QUANTA (Moleculart Simulations Inc+, San Diego)+ After positional refinement using X-PLOR (Brünger, 1992), model and experimental phases were combined using SIGMAA (Collaborative Computational Project, Number 4, 1994)+ These steps were repeated ten times until about 90% of the whole molecule were traced+ In the next stage, phases were calculated from a model structure after positional refinement and were refined by solvent flattening and histogram matching with DM+ A mask, calculated from the model structure (sphere radius ϭ 4+0 Å), was used for this phase refinement and the solvent content was set to be 40% of the unit cell+ These steps were repeated 24 times until the whole molecule was traced+ Finally, water molecules were added to the model structure and positional and B-factor refinements were performed several times+ The correctness of the model structure was confirmed by omit map+ The final R-factor was 23+2% (R free ϭ 30+5% calculated from 5% of the data) at 2+6-10 Å resolution+ Analysis using PROCHECK (Laskowski et al+, 1993) showed that no residues fell outside of the allowed region of the Ramachandran plot+ The final structure includes 1,478 nonhydrogen atoms and 84 water molecules+ The structure coordinates have been deposited with the Protein Data Bank (http://www+rcsb+org/pdb; accession code 1EH1)+ Site-directed mutagenesis ttRRF variants were manipulated by site-directed mutagenesis using polymerase chain reaction (PCR)+ The loop 1 mutations were designed in sense oligonucleotides: R32A, 59-GGGGCTCGAGGTCCTGGAGCACAACCTGGCAGGCC TCGCCACCGGCCGCGCCAACCCCG-39; R32S, 59-GGGG CTCGAGGTCCTGGAGCACAACCTGGCAGGCCTCTCCAC CGGCCGCGCCAACCCCG-39; and R32G, 59-GGGGCTCG AGGTCCTGGAGCACAACCTGGCAGGCCTCGGCACCGG CCGCGCCAACCCCG-39+ These mutation fragments amplified by PCR using these sense primers and a universal (antisense) primer, and their XhoI-BamHI digests were ligated into the same sites of plasmid pIQV-ttRRF+ The loop 2 mutations were designed in sense oligonucleotides: I103A, 59-GGACGCGTTATACATCAACGCCCCGCCCCTCACGGA GGA-39; P104A, 59-GGACGCGTTATACATCAACATCGCGC CCCTCACGGAGGAAAG-39; P105A, 59-GGACGCGTTATA CATCAACATCCCGGCCCTCACGGAGGAAAGGCG-39; and L106A, 59-GGACGCGTTATACATCAACATCCCGCCCGCCA CGGAGGAAAGGCGAAAG-39+ These altered C-terminal segments were amplified by PCR using these sense primers and a universal (antisense) primer, and their MluI-BamHI digests were ligated into the same sites of plasmid pIQV-ttRRF+ The C-terminal ⌬C5 deletion (Glu181 r amber allele) was introduced into relevant variants by substituting the StuI-BamHI (⌬C5) segment from ttRRF*181 (Fujiwara et al+, 1999) for the wild-type segment, and tested for the activity under nonsuppressor (sup 0 ) conditions+ The Glu182 r Ser variant was generated by replacing the wild-type StuI-BamHI sequence with the mutant segment amplified by PCR using a universal upstream ...…”
Section: Structure Determination and Refinementmentioning
confidence: 99%
See 1 more Smart Citation
“…The rationale of mapping the ribosome-binding site in this study was, first, to isolate a variant of E. coli RRF that is partially defective in the ribosome binding and, second, to select suppressor mutants that regain the activity to bind to the ribosome via secondary changes in the hope that these compensatory mutations will alter the site for the ribosome binding in a way that increases the binding capacity ("gain-of-function" phenotype)+ It is known that RRF is essential for bacterial growth (Janosi et al+, 1998), and that the activity can be modulated by alteration in the C-terminal residues (Fujiwara et al+, 1999)+ Accordingly, to screen for a reduced ribosome association form of RRF, we constructed a series of C-terminal deletions at two-amino-acid intervals in the RRF gene cloned in plasmid pIQV27 (renamed from pSUIQ; Uno et al+, 1996) by nonsense substitutions (i+e+, tandem UAA stop codons)+ These C-terminal truncations were examined for the complementation activity upon transformation of a temperaturesensitive RRF strain YN3576 (Fujiwara et al+, 1999) or a RRF knockout strain (K+ Ito and Y+ Nakamura, unpubl+)+ One such deletion, ⌬C9, lacking 9 amino acids, seemed to be appropriate as a parental form to select compensatory changes, given that its primary defect is in the ribosome binding, because the ⌬C9 protein shows a temperature-sensitive phenotype, active at 30 8C but inactive at 42 8C in complementation (Fig+ 1A), and a deletion mutant (in which tandem UAA stop codons substitute for the C-terminal 9 amino acids) would never revert to a wild-type form when suppressors are selected as survivors at 42 8C+ RRF variant defective in the ribosome binding RRF is known to trigger a dissociation of the polysome complex into monosomes in vitro (Hirashima & Kaji, 1972)+ Hence, first, the ⌬C9 and wild-type RRF proteins were overproduced and purified to homogeneity to test the protein activity in the conventional polysome breakdown assay+ (We assume that the appearance of monosome fractions in the presence of RRF does not necessarily reflect the primary action mechanism of RRF because the assay uses crude polysome fractions under the condition that favors the reassembly of 30S and 50S subunits to 70S ribosomes+) The polysome fraction was prepared from exponentially growing E. coli cells (MRE600), incubated with wild-type and ⌬C9 RRF proteins, and analyzed by sucrose density gradient centrifugation+ As shown in Figure 2, wild-type RRF catalyzed polysome-to-monosome conversion, but the ⌬C9 variant failed to do so+ Next, we investigated whether or not the wild-type protein binds to the ribosome and, if so, if the ⌬C9 protein binds to the ribosome as efficiently as does the wild type+ The conventional sucrose density gradient analysis detects the fraction of […”
Section: The Rationale Of Functional Mappingmentioning
confidence: 99%